Hemimegalencephaly and intractable seizures associated with the NPRL3 gene variant in a newborn: A case report. Issue 7 (22nd March 2021) - Chandrasekar, Indira; Tourney, Anne; Loo, Kamela; Carmichael, Jason; James, Kiely; Ellsworth, Katarzyna A.; Dimmock, David; Joseph, Maries
Abstract: Hemimegalencephaly (HME) is a rare hamartomatous congenital malformation of the brain characterized by dysplastic overgrowth of either one of the cerebral hemispheres. HME is associated with early onset seizures, abnormal neurological findings, and with subsequent cognitive and behavioral disabilities. Seizures associated with HME are often refractory to antiepileptic medications. Hemispherectomy is usually necessary to provide effective seizure control. The exact etiology of HME is not fully understood, but involves a disturbance in early brain development and likely involves genes responsible for patterning and symmetry of the brain. We present a female newborn who had refractory seizures due to HME. Whole genome sequencing revealed a novel, likely pathogenic, maternally inherited, 3Kb deletion encompassing exon 5 of the NPRL3 gene (chr16:161898‐164745x1). The NPRL3 gene encodes for a nitrogen permease regulator 3‐like protein, a subunit of the GATOR complex, which regulates the mTOR signaling pathway. A trial of mTOR inhibitor drug, Sirolimus, did not improve her seizure control. Functional hemispherectomy at 3 months of age resulted in total abatement of clinical seizures.